A farmer survey, to determine the way potato farmers perceived the leafininer fly and methods they employed to control the pest, was conducted in ten highland vegetable production centers in five provinces jhm June to September 1998. The total number of potato farmers interviewed was 309. The study revealed that the farmers were familiar with the leafininer as a new pest that have caused heavy damage since 3-6 years ago. However, only few farmers (5.5%) were knowledgeable that L. huidobrensis wa - Aunu Rauf (Buletin Hama dan Penyakit Tumbuhan, 1999)
A farmer survey, to determine the way potato farmers perceived the leafininer fly and methods they employed to control the pest, was conducted in ten highland vegetable production centers in five provinces jhm June to September 1998. The total number of potato farmers interviewed was 309. The study revealed that the farmers were familiar with the leafininer as a new pest that have caused heavy damage since 3-6 years ago. However, only few farmers (5.5%) were knowledgeable that L. huidobrensis was an exotic pest. Most farmers (>75%) reported that leafininer infestation caused more than 40% yield losses, and the crops have to be harvested 2-4 weeks earlier than was the nomal practice. All respondents applied insecticides to control the leafininer twice a week. Insecticides mostly used were pyrethmids and organophosphates. Selection of pesticides was based on farmer's own experiences, other farmers experiences, and based on suggestion jhm pesticide kiosk's owners. Although insecticides were used intensively, most farmers (72%) were dissatisfied with the efficacy of control. Biological control with parasitoids may pegom satisfatorily only if it B accompanied by minimizing insecticide use.